msp1, msp2, and glurp genotyping to differentiate Plasmodium falciparum recrudescence from reinfections during prevention of reestablishment phase, Sri Lanka, 2014–2019 - Kumudunayana T. Gunasekera; Risintha G. Premaratne; Shiroma M. Handunnetti; Jagathpriya Weerasena; Sunil Premawansa; Deepika S. Fernando (Malaria Journal, 2024)
Abstract Background Sri Lanka after eliminating malaria in 2012, is in the prevention of re-establishment (POR) phase. Being a tropical country with high malariogenic potential, maintaining vigilance is important. All malaria cases are investigated epidemiologically and followed up by integrated drug efficacy surveillance (iDES). Occasionally, that alone is not adequate to differentiate Plasmodium falciparum reinfections from recrudescences. This study evaluated the World Health Organization and Medicines for Malaria Venture (MMV) recommended genotyping protocol for the merozoite surface proteins (msp1, msp2) and the glutamate-rich protein (glurp) to discriminate P. falciparum recrudescence from reinfection in POR phase. Methods All P. falciparum patients detected from April 2014 to December 2019 were included in this study. Patients were treated and followed up by iDES up to 28 days and were advised to get tested if they develop fever at any time over the following year. Basic socio-demographic information including history of travel was obtained. Details of the malariogenic potential and reactive entomological and parasitological surveillance carried out by the Anti Malaria Campaign to exclude the possibility of local transmission were also collected. The msp1, msp2, and glurp genotyping was performed for initial and any recurrent infections. Classification of recurrent infections as recrudescence or reinfection was done based on epidemiological findings and was compared with the genotyping outcome. Results Among 106 P. falciparum patients, six had recurrent infections. All the initial infections were imported, with a history of travel to malaria endemic countries. In all instances, the reactive entomological and parasitological surveillance had no evidence for local transmission. Five recurrences occurred within 28 days of follow-up and were classified as recrudescence. They have not travelled to malaria endemic countries between the initial and recurrent infections. The other had a recurrent infection after 105 days. It was assumed a reinfection, as he had travelled to the same malaria endemic country in between the two malaria attacks. Genotyping confirmed the recrudescence and the reinfection. Conclusions The msp1, msp2 and glurp genotyping method accurately differentiated reinfections from recrudescence. Since reinfection without a history of travel to a malaria endemic country would mean local transmission, combining genotyping outcome with epidemiological findings will assist classifying malaria cases without any ambiguity.